2016
DOI: 10.1016/j.kint.2016.07.015
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of microRNA-486-5p from human endothelial colony forming cell–derived exosomes reduces ischemic kidney injury

Abstract: Administration of human cord blood endothelial colony-forming cells (ECFCs) or their exosomes protects mice against kidney ischemia/reperfusion injury. Here we studied the microRNA (miRNA) content of ECFC exosomes and the role of miRNA transfer in kidney and endothelial cell protection. ECFC exosomes were enriched in miR-486-5p, which targets the phosphatase and tensin homolog (PTEN) and the Akt pathway. In cultured endothelial cells exposed to hypoxia, incubation with ECFC exosomes increased miR-486-5p, decre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
179
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 194 publications
(183 citation statements)
references
References 37 publications
4
179
0
Order By: Relevance
“…On the other hand, suppression of miR-486 further aggravated hypoxia-induced injury. These results were consistent with previous studies that transfecting of miR-486-5p could reduce ischemic kidney injury [17] and miR-486 attenuated cardiac myocyte damage in vitro [18]. In addition, miR-486 is a potent modulator in cardiac/skeletal muscle [19] and studies from Zhang et al found that upregulation of circulating miR-486 in AMI patients may be related to cardiac hypertrophy [20].…”
Section: Discussionsupporting
confidence: 92%
“…On the other hand, suppression of miR-486 further aggravated hypoxia-induced injury. These results were consistent with previous studies that transfecting of miR-486-5p could reduce ischemic kidney injury [17] and miR-486 attenuated cardiac myocyte damage in vitro [18]. In addition, miR-486 is a potent modulator in cardiac/skeletal muscle [19] and studies from Zhang et al found that upregulation of circulating miR-486 in AMI patients may be related to cardiac hypertrophy [20].…”
Section: Discussionsupporting
confidence: 92%
“…For instance, transfer of miR-489 expression from human cord blood endothelial colony-forming cell-derived exosomes reduced ischemic kidney injury by targeting phosphatase and tensin homolog (PTEN) through activation of Akt pathway [29]. miR-107 induced TNF-α secretion by targeting Dual-specificity phosphatase 7(DUSP7) in endothelial cells, triggering tubular cell injury in septic AKI [30].…”
Section: Discussionmentioning
confidence: 99%
“…Podocyte MP were labelled with PKH26 as described [28]. Briefly, podocyte MPs were labelled with the red fluorescent dye PKH26 (Sigma) for 5 min at room temperature according to manufacturer’s instructions.…”
Section: Methodsmentioning
confidence: 99%